Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1155/s1064744903000085
|View full text |Cite
|
Sign up to set email alerts
|

Abscess in Adenomyosis Mimicking a Malignancy in a54‐Year‐Old Woman

Abstract: Background:Although there are a few reports describing abscess formation in endometriotic foci no report of abscess formation arising de novo within adenomyosis appears in the literature. Preoperative diagnosis of adenomyosis is frequently difficult because of non-specific signs and symptoms. Synchronous pelvic pathologies such as leiomyoma, endometrial polyp, endometrial hyperplasia, as well as endometrial cancer may cause differential diagnostic problems. Case: A 54-year-old postmenopausal woman complaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…The functional changes that occur as a result of adenomyosis during pregnancy and after delivery include decidualization and hemorrhage within the adenomyosis. As adenomyosis is characterized by a chronic inflammatory disease, it could be responsible for severe infection and abscess formation within the adenomyotic foci . The present results show an increase in the incidence of intrauterine infection (7.3%; 19/262) in pregnant women with adenomyosis.…”
Section: Discussionsupporting
confidence: 50%
“…The functional changes that occur as a result of adenomyosis during pregnancy and after delivery include decidualization and hemorrhage within the adenomyosis. As adenomyosis is characterized by a chronic inflammatory disease, it could be responsible for severe infection and abscess formation within the adenomyotic foci . The present results show an increase in the incidence of intrauterine infection (7.3%; 19/262) in pregnant women with adenomyosis.…”
Section: Discussionsupporting
confidence: 50%
“…As adenomyosis is characterized by a chronic inflammatory disease, it could be responsible for severe infection and abscess formation within the adenomyotic foci. 25,26 The present results show an increase in the incidence of intrauterine infection . [27][28][29][30] In the present study, there were no data to suggest that conservative surgery as a pretreatment for adenomyosis before pregnancy reduced the incidence of pregnancy complications.…”
supporting
confidence: 58%
“…The uterine and extrauterine adenomyomas were abscessed in our case. Although abscess formation is reported in the endometriomas [3, 4], only Erguvan et al reported an abscessed adenomyosis [5]. In Martino et al's case the abscess occurred iatrogenically following fine needle aspiration [3].…”
Section: Discussionmentioning
confidence: 99%
“…The downgrowth and invagination of the basalis endometrium into the myometrium are the current developmental theory [2]. Although there are few reports describing abscess formation in endometriosis, there is only one reported case of abscessed adenomyosis [35]. Adenomyomas may be located within the myometrium, or it may involve or originate in the endometrium and grow as a polyp [1, 6].…”
Section: Introductionmentioning
confidence: 99%